Prevalence and policy of occupational violence against oral healthcare workers: systematic review and meta-analysis - Nada O. Binmadi; Jazia A. Alblowi (BMC, 2019)
Abstract Background Occupational violence is considered unlawful in professional environments worldwide. In the healthcare industry, including dentistry, the safety of workers is essential, and it is of the utmost importance to ensure patient and employee safety and provide quality care. This study aimed to evaluate the prevalence of violence and associated workplace policies among oral healthcare professionals. Additionally, it aimed to identify the factors associated with violence and their impact on oral healthcare workers. Methods A systematic review and analysis of the literature was conducted using PubMed, ScienceDirect, Scopus, Web of Science, Cochrane Library and ProQuest. Original articles written in English and published between January 1992 and August 2019 were included in the analysis. Results A total of 980 articles were found, and eight were selected for analysis. The violence experienced by healthcare workers included both physical and non-physical forms, such as shouting, bullying, and threatening; it also included sexual harassment. The impact of violence on workers manifested as impaired quality of work, psychological problems, and, although rare, quitting the job. With regard to dental healthcare, awareness of occupational violence policies among dental professionals has not been previously reported in the literature. Conclusions The increasing incidence of occupational violence against oral healthcare workers indicates the need for the implementation of better protective measures to create a safe working environment for dental professionals. There is a current need for increasing awareness of workplace violence policies and for the detection and reporting of aggression and violence at dental facilities.